Finnsheep and their crosses under subtropical conditions - A. M. Aboul-Naga (Agricultural and Food Science, 1988)
Finnsheep (F) have been introduced to eight countries in the subtropical Near East region over the last two decades. Those trials aiming at breeding pure F under the subtropical conditions were generally not successful. Pure F faced problems of adaptability to the subtropical environmental conditions, however, bad management and some health problems (especially Pneumonia) contributed significantly to the failure of some trials. On the other hand, crossbreeding trials with F in the region were generally successful. F-crosses proved to be well adapted to heat stress and exposure to solar radiation compared with the local breeds. Number of lambs born/ewe lambed was improved in F-crosses, as compared to local breeds, by 18—75 %in the first cross and 10—38 % in the 1/4 F. F-crossbred ewes showed encouraging results in their ability to breed more than once/year, especially those with lower F-blood (1/4 F). Number of lambs born/ewe/year in accelerated lambing systems ranged from 1.91 to 2.72 in the first cross and from 1.67 to 2.18 in 1/4 F either in experimental farms or at the producers. Crossing fat tail sheep with F substantially decreased fat in the tail of the crossbreeds, while it increased significantly internal fat and total fat percentage in the carcass.